A Prospective, Randomized, Controlled, Two-Center, International Trial Comparing the Fibular Nail With Open Reduction and Internal Fixation for Unstable Ankle Fractures in Younger Patients. Issue 1 (January 2022) - White, Tim O.; Bugler, Kate E.; Olsen, Lucy; Lundholm, Linea Holck; Holck, Kim; Madsen, Bjoern Lindegaard; Duckworth, Andrew D.
Abstract : Objective: To compare the outcome of fibular nailing with plate fixation for unstable fractures of the ankle in a cohort of patients under the age of 65 years. Setting: 2 international university trauma centers. Patients/Participants: One hundred twenty-five patients who were 18–64 years of age with an acute unstable fracture of the ankle were included in the study. Intervention: Patients were randomized to fixation with a fibular nail (n = 63) or plate (n = 62) and were reviewed at 6 weeks, 3 months, 6 months, 1 year, and 2 years after surgery. Main Outcome Measurements: The primary outcome measure was the Olerud and Molander score at 1 year. Secondary outcomes were the rates of complications and reinterventions. Results: There was no difference between the 2 groups with respect to the primary outcome measure [mean Olerud and Molander score 78.4 in the nail group vs. 80.2 in the plate group ( P = 0.621)]. Wound infections occurred in 2 patients who were treated with a nail and 9 patients who were treated with a plate, but this did not reach statistical significance. No difference was seen in the overall rate of complications and reinterventions between groups [28.6% in the nail group vs. 29% in the plate group ( P = 0.955)]. Conclusions: In younger patients with ankle fractures, no difference was found in the patient-reported outcome between fibular nail and plate fixation at 1 year after surgery. The fibular nail is an effective and safe option for the stabilization of ankle fractures in younger patients, although the benefits associated with reduced wound complications are not as apparent as for elderly patients. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.